2000
DOI: 10.1128/jvi.74.12.5679-5690.2000
|View full text |Cite
|
Sign up to set email alerts
|

Differential Narrow Focusing of Immunodominant Human Immunodeficiency Virus Gag-Specific Cytotoxic T-Lymphocyte Responses in Infected African and Caucasoid Adults and Children

Abstract: Gag and p24 Gag sequences tested contain two-thirds of the dominant Gag-specific epitopes, irrespective of the clade, ethnicity, or age group studied. However, there were distinctive differences between the dominant responses made by Caucasoids and Africans. Dominant responses in Caucasoids were more often within p17Gag peptide residues 16 to 30 (38 versus 12%; P < 0.01), while p24 Gag peptide residues 41 to 60 contained the dominant Gag epitope more often in the African subjects tested (39 versus 4%; P < 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 65 publications
11
95
0
Order By: Relevance
“…Two separate studies have shown that while p17 is highly targeted in subtype B HIV-1-infected individuals, p24 was mostly targeted by subtype C-infected individuals in Africa (39,40). In contrast, we identified epitope-rich regions in both p17 and p24 that are targeted by CD8 ϩ T cells, and the peptide stretch, TGTEELRSLYNTVATLYCVHAGIEV, in p17 was recognized at the highest frequency (35%) and contained multiple epitopes.…”
Section: Discussionmentioning
confidence: 77%
“…Two separate studies have shown that while p17 is highly targeted in subtype B HIV-1-infected individuals, p24 was mostly targeted by subtype C-infected individuals in Africa (39,40). In contrast, we identified epitope-rich regions in both p17 and p24 that are targeted by CD8 ϩ T cells, and the peptide stretch, TGTEELRSLYNTVATLYCVHAGIEV, in p17 was recognized at the highest frequency (35%) and contained multiple epitopes.…”
Section: Discussionmentioning
confidence: 77%
“…Increasing evidence suggests that a comprehensive assessment of CD8 ϩ T cell responses against HIV-1 is necessary to interpret the entire magnitude and breadth of these responses (8,16). We have recently demonstrated that the use of overlapping peptide spanning the HIV-1 structural as well as regulatory proteins allows for a detailed characterization of HIV-1-specific CTL responses and the identification of novel CTL epitopes within these proteins (9,16,23,24,27,36). However, the relative contribution of CTL responses directed against the accessory HIV-1 proteins Vpr, Vpu, and Vif have not been studied to date.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were added to the wells at 50,000 -100,000 cells/well. The plates were incubated at 37°C, 5% CO 2 overnight (14 -16 h) and then processed as described (23,24). IFN-␥-producing cells were counted by direct visualization and are expressed as spot-forming cells (SFCs) per 10 6 cells.…”
Section: Elispot Assaymentioning
confidence: 99%
“…The region of HIV-1 Gag corresponding to peptide 46 contributes to the total immune response in HIV-1 infection in terms of frequency of recognition (35), immunodominance (18,36), and avidity (22). This frequently targeted and highly immunogenic region of Gag can be restricted by both CD4 (21, 37) and CD8 (35) T cells as well as by a variety of HLA haplotypes (38).…”
Section: Figurementioning
confidence: 99%